The Impact of Capital Structure and Liquidity on Firm Value with Profitability as an Intervening Variable: A Study on LQ45 Companies - Qinthara, Aisyah Noor; Ramadhan, Nanda Galih; Mardiyani; Parlina, Nurhana Dhea (Ilomata International Journal of Tax and Accounting, 2024)
The objective of this study is to investigate how capital structure and liquidity affect company value in companies listed on the LQ45, using profitability as an intervening variable. According to the purposive sampling technique, 31 companies were selected as samples with an observation period during 2021–2023, yielding 93 observation data. The study uses a quantitative method with a causal associative approach, and the population comprises of organizations that were on the LQ45 list in 2023. The data was analyzed using path analysis using the LISREL 8.8 program. According to the findings, capital structure and liquidity had no significant effect on profitability or company value, and profitability did not mediate the effect of the two factors on firm value. This conclusion shows that current investors tend to pay more attention to the company's ability to make profits, as well as other essential elements such as growth potential, innovation, and capital business sustainability. This study recommends that companies focus more on optimizing profitability and developing non-financial aspects such as growth potential, innovation, and business sustainability to enhance company's value.